Repetition and its Effect on the Text Cohesion in the Victory Speech of the Supreme Reference: Applied Study in the Text Syntax - Kareem Hassan, Raad (Journal of College of Education, 2020)
This research deals with a kind of text cohesion which is repetition. It represents a great importance in in the consistency of the structural cohesion among the words and in exploring the role of repetition and its effect on  the text cohesion in the Victory Speech of the Supreme Reference in the Holy Najaf as it creates a semantic dimension among the  text elements and aesthetic benefits help to increase the efficiency of the text syntax.
Keywords: : Repetition and its Effect on the Text Cohesion in the Victory Speech